Lifetime prevalence and correlates of self-harm and suicide attempts among male prisoners with histories of injecting drug use - Ashleigh C. Stewart; Reece Cossar; Paul Dietze; Gregory Armstrong; Michael Curtis; Stuart A. Kinner; James R. P. Ogloff; Amy Kirwan; Mark Stoové (BMC, 2018)
Abstract Background Histories of self-harm and suicide attempts are common among people in prison in Australia, and substance dependence is an established risk factor for these lifetime experiences. We describe the prevalence of self-reported history of non-suicidal self-injury (NSSI) and suicide attempts in a cohort of men with recent histories of injecting drug use (IDU) imprisoned in Victoria, Australia. Baseline interviews from the Prison and Transition Health (PATH) prospective cohort study were conducted in the weeks prior to release from prison among 400 incarcerated men who reported regular IDU in the six months prior to incarceration. Results Participants completed a researcher-administered structured questionnaire that collected information on sociodemographics, substance use patterns, and physical and mental health indicators. More than one third (37%) reported a history of NSSI and almost half of participants (47%) reported a history of suicide attempts. In multivariable Poisson regression models, a history of NSSI was associated with: being aged 30-39 years; moving accommodation three or more times in the year prior to current sentence; self-reporting a history of mental illness diagnosis; current poor psychiatric well-being; and self-reporting three or more previous drug overdoses. History of suicide attempts was significantly associated with: self-reporting a history of mental illness diagnosis; current poor psychiatric well-being; and self-reporting a history of 1-2 and > 3 drug overdoses. Conclusion We observed a disconcertingly high lifetime prevalence of non-suicidal self-injury and suicide attempts among incarcerated males with a history of recent regular injecting drug use. Significant associations with indicators of mental illness and drug related harms support the need to prioritise in-prison screening and early intervention to reduce the risk of future harms for this population.